Socioeconomic and Demographic Risk Factors Affecting Adult Participants With Hypertension in Bangladesh: A Cross-Sectional Study - Sohani Afroja; Rashedul Islam; Uttam Kumar Majumder (Advances in Public Health)
Conclusion: These findings suggested that age, overweight, marital status, wealth index, education, and diabetes were significant risk factors for hypertension and prehypertension. The study’s findings will help Bangladesh’s government and policymakers develop effective policies and initiatives to prevent hypertension in adults.